Targeted protein degradation: from small molecules to complex organelles—a Keystone Symposia report. Issue 1 (8th January 2022) - Cable, Jennifer; Weber‐Ban, Eilika; Clausen, Tim; Walters, Kylie J.; Sharon, Michal; Finley, Daniel J.; Gu, Yangnan; Hanna, John; Feng, Yue; Martens, Sascha; Simonsen, Anne; Hansen, Malene; et al.
Abstract: Targeted protein degradation is critical for proper cellular function and development. Protein degradation pathways, such as the ubiquitin proteasomes system, autophagy, and endosome–lysosome pathway, must be tightly regulated to ensure proper elimination of misfolded and aggregated proteins and regulate changing protein levels during cellular differentiation, while ensuring that normal proteins remain unscathed. Protein degradation pathways have also garnered interest as a means to selectively eliminate target proteins that may be difficult to inhibit via other mechanisms. On June 7 and 8, 2021, several experts in protein degradation pathways met virtually for the Keystone eSymposium "Targeting protein degradation: from small molecules to complex organelles." The event brought together researchers working in different protein degradation pathways in an effort to begin to develop a holistic, integrated vision of protein degradation that incorporates all the major pathways to understand how changes in them can lead to disease pathology and, alternatively, how they can be leveraged for novel therapeutics. Abstract : Protein quality control is critical to maintain proper cellular function and development. Accumulation and subsequent aggregation of misfolded proteins is a hallmark of several diseases. Cells have devised several mechanisms to identify misfolded proteins and understanding these protein clearance pathways is key to not only understanding how their dysfunction is involved in disease pathology but also to harnessing these systems for therapeutic applications. On Demand : https://keysym.us/21EK40NYAS